Changing trends of mental and behavioral responses and associations during the COVID-19 epidemic in China: a panel study. Issue 2 (16th March 2021) - Yang, Xiaozhao Yousef; Peng, Sihui; Yang, Tingzhong; Cottrell, Randall R
Abstract: This prospective observational study examined changing trends in mental and behavioral responses, and their association with perceived risk, severity, self-efficacy and isolation status during the Chinese COVID-19 epidemic. There were five waves of interviews. Descriptive statistics and non-parametric test methods were used for data analysis. Participants numbered 150 for the linkable baseline survey and 102 completed all 5 survey waves and were included in the analysis. Mental stress, emotional status and lifestyle manifested a statistically significant downwards trend across the total period of this panel study. The number of reported new confirmed patients perceived high risk and perceived severity were positively associated with mental stress, emotional status and lifestyle. Self-efficacy was negatively associated with each type of mental and behavioral response. The more time people were confined to their home, the more serious the emotional and lifestyle problems. Dose-response relationships were noted between the number of reported new confirmed patients and mental stress, emotional status and lifestyle during the five observation points. This study yielded new information about mental and behavioral responses among Chinese people during the COVID-19 epidemic. Policy changes and health education are essential for minimizing the adverse health effects of these responses.